Epigenetic modification in histone deacetylase deletion strain of Calcarisporium arbuscula leads to diverse diterpenoids - Jian Bai; Rong Mu; Man Dou; Daojiang Yan; Bingyu Liu; Qian Wei; Jun Wan; Yi Tang; Youcai Hu (Elsevier, 2018)
Epigenetic modifications have been proved to be a powerful way to activate silent gene clusters and lead to diverse secondary metabolites in fungi. Previously, inactivation of a histone H3 deacetylase in Calcarisporium arbuscula had led to pleiotropic activation and overexpression of more than 75% of the biosynthetic genes and isolation of ten compounds. Further investigation of the crude extract of C. arbuscula ΔhdaA strain resulted in the isolation of twelve new diterpenoids including three cassanes (1−3), one cleistanthane (4), six pimaranes (5−10), and two isopimaranes (11 and 12) along with two know cleistanthane analogues. Their structures were elucidated by extensive NMR spectroscopic data analysis. Compounds 2 and 4 showed potent inhibitory effects on the expression of MMP1 and MMP2 (matrix metalloproteinases family) in human breast cancer (MCF-7) cells. KEY WORDS: Calcarisporium arbuscula, Calcarisporic acids, Pimarane, Diterpenoid, Matrix metalloproteinases inhibitor, Epigenetic genome mining